Optical, mechanical, structural, and antimicrobial properties of tamarind kernel powder, halloysite, and cinnamaldehyde nanocomposite films. (3rd May 2022) - Nath, Debarshi; Santhosh, Ravichandran; Ahmed, Jasim; Sarkar, Preetam
Abstract: With paramount pressures from the laws enforcing agents and the general public in greenhouse gas emission and environmental issues, the importance of biodegradable materials with suitable properties for potential applications in the food packaging has received serious attention. In this work, tamarind kernel powder (TKP)/halloysite (HS)/cinnamaldehyde (CND) nanocomposite (NC) films were successfully developed using the solution casting method. CND with selected concentrations (0.5%–3%, w/w) were loaded into TKP (5% w/w)/HS (2% w/w) matrix. The NC films were characterized by optical measurement (e.g., color, transparency), scanning electron microscopy (SEM), X‐ray diffraction (XRD), Fourier transform infrared spectrophotometer (FTIR), barrier, and mechanical properties. The CND concentration significantly influenced the film properties. The developed nanocomposite films exhibited excellent antimicrobial efficacy against Gram‐positive and Gram‐negative foodborne pathogens ( Bacillus cereus, Listeria monocytogenes, Escherichia coli, and Salmonella Typhimurium). Film with 2% CND was found to be a good candidate for active packaging application. Practical applications: In the present times, there have been increased interests in the fabrication of biodegradable films for food packaging applications to reduce the usage of plastic‐based materials. This trend has urged researchers to develop bio‐based packaging materials with increased functionality. Tamarind kernel powder possesses excellent film‐forming properties, and their reinforcement with nanoclays and essential oil makes them useful as a food packaging material. In the present study, the optical, barrier, and antimicrobial properties of tamarind kernel powder films were improved by incorporating halloysite nanoclay and cinnamaldehyde. Therefore, the developed antimicrobial films with improved functionality have high potential as a food packaging material. Abstract : An overview of film formation and characterization of nanocomposite films from tamarind kernel powder/halloysite/cinnamaldehyde.